La bourrée et ses mythes - Françoise Étay (In Situ)
Since the 19th century, the presumed antiquity of the bourrée, whether danced, sung or instrumental, has fascinated many observers. The collectors of the late twentieth century may have seemed more rigorous than their predecessors, generally - not always - taking a cautious distance from hazardous hypotheses evoking prehistoric or, more modestly, Gallic origins. But, for many of them, a deep seniority, spanning a considerable number of generations, was beyond doubt. This postulate has played on the way in which the practices encountered in rural areas have been perceived, and, therefore, on the conduct of collections. It then influenced many musical or choreographic reinterpretations. And it is often it which, more or less consciously, is at work behind differences that one might think are limited to aesthetic choices.Nowadays, we can spot new ways of playing and dancing bourrée in balls. The proximity to the models collected has weakened over the years and some dancers even claim a break with them. Yet here again, behind distant artistic and intellectual postures, it is indeed conceptions of antiquity and modernity that we can sense.